Cardiorespiratory and perceptual responses of two interval training and a continuous training protocol in healthy young men. Issue 5 (28th May 2019) - Naves, João Pedro Araújo; Rebelo, Ana Cristina Silva; Silva, Lucas Raphael Bento E; Silva, Maria Sebastiana; Ramirez-Campillo, Rodrigo; Ramírez-Vélez, Robinson; Gentil, Paulo
Abstract: High Intensity Interval Training (HIIT) can be performed with different effort to rest time-configurations, and this can largely influence training responses. The purpose of the study was to compare the acute physiological responses of two HIIT and one moderate intensity continuous training (MICT) protocol in young men. A randomised cross-over study with 10 men [age, 28.3 ± 5.5years; weight, 77.3 ± 9.3 kg; height, 1.8 ± 0.1 m; peak oxygen consumption (VO2 peak), 44 ± 11 mL.kg −1 .min −1 ]. Participants performed a cardiorespiratory test on a treadmill to assess VO2 peak, velocity associated with VO2 peak ( v VO2 peak), peak heart rate (HRpeak) and perceived exertion (RPE). Then participants performed three protocols equated by distance: Short HIIT (29 bouts of 30s at v VO2 peak, interspersed by 30s of passive recovery, 29 min in total), Long HIIT (3 bouts of 4 min at 90% of v VO2 peak, interspersed by 3 min of recovery at 60% of v VO2 peak, 21 min in total) and MICT (21 min at 70% of v VO2 peak). The protocols were performed in a randomised order with ≥48 h between them. VO2, HRpeak and RPE were compared. VO2 peak in Long HIIT was significantly higher than Short HIIT and MICT (43 ± 11 vs 32 ± 8 and 37 ± 8 mL.kg −1 .min −1, respectively, P < 0.05), as well as peak HR (181 ± 10 vs 168 ± 8 and 167 ± 11, respectively, P < 0.05), and RPE (17 ± 4 vs 14 ± 4 and 15 ± 4, respectively, P < 0.05), with no difference between Short HIIT and MICT. In conclusion, Long HIIT promoted higher acute increases in VO2, HR and RPE than Short HIIT and MICT, suggesting a higher demand on the cardiorespiratory system. Short HIIT and MICT presented similar physiologic and perceptual responses, despite Short HIIT being performed at higher velocities.